Philosophical Sufism and Legal Culture in Nusantara: An Epistemological Review - Wasitaatmadja, Fokky Fuad; Susetio, Wasis (Al-Risalah, 2020)
A research on the relation between sufism, sharia, and the local culture is essential for some reasons. First, Islamic philosophy and customary law (or the law of the peoples) are perceived as opposing each other. Second, Islamic philosophy, also in Geertz’s theory, regards Islam merely as the structure of religious orthodoxy. Third: the structure of Islamic orthodoxy, often portrayed as a highly rigid one, is often (seen as) conflicting with sufism in the world of Islamic scholarship. This paper aims to determine the dynamic relation between the spiritual values ​​of Sufism and traditional values ​​surviving in the so-called Nusantara legal culture. It also elaborates on the extent to which a distinct epistemology typical to sufism may contribute to enriching the cultural space of Nusantara law. As normative legal research, this paper employs the principle of legal culture developed by Lawrence M. Friedman. It concludes that the spiritual values ​​of sufism are not conflicting with the principles of Islamic jurisprudence. It would also argue that the construction of Nusantara legal culture has a unique character resulted from dynamic interaction of traditional values, on the one hand, and sufism on the other.